2016
DOI: 10.1371/journal.pone.0164509
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Sensitive Fluorescent Dyes Fluo-4 and Fura Red under Pressure: Behaviour of Fluorescence and Buffer Properties under Hydrostatic Pressures up to 200 MPa

Abstract: The fluorescent Ca2+ sensitive dyes Fura Red (ratiometric) and Fluo-4 (non-ratiometric) are widely utilized for the optical assessment of Ca2+ fluctuations in vitro as well as in situ. The fluorescent behavior of these dyes is strongly depends on temperature, pH, ionic strength and pressure. It is crucial to understand the response of these dyes to pressure when applying calcium imaging technologies in the field of high pressure bioscience. Therefore, we use an optically accessible pressure vessel to pressuriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…To first check the Fluo4 fluorescence behavior using our hydrostatic pressure spectroscopic instruments (see Figure S1 in the SI), we measured fluorescence spectra of Fluo4 (a corresponding derivative of Fluo4-AM) in the L-15 medium containing 1.3 mM CaCl 2 in the range of 0.1–300 MPa (Figure a). Fluorescence decreasing upon hydrostatic pressurization was observed as was the case in the Ca 2+ concentration in cytosol (∼100 nM) reported previously, for which the pressure-promoted dissociation of Ca 2+ from Fluo4 based on the positive Δ V ° value is responsible. In addition, we used DAPI (Figure b, right) as a fluorescent indicator for evaluating a cell death, the dye of which intercalates into DNA of a dead cell to fluoresce.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…To first check the Fluo4 fluorescence behavior using our hydrostatic pressure spectroscopic instruments (see Figure S1 in the SI), we measured fluorescence spectra of Fluo4 (a corresponding derivative of Fluo4-AM) in the L-15 medium containing 1.3 mM CaCl 2 in the range of 0.1–300 MPa (Figure a). Fluorescence decreasing upon hydrostatic pressurization was observed as was the case in the Ca 2+ concentration in cytosol (∼100 nM) reported previously, for which the pressure-promoted dissociation of Ca 2+ from Fluo4 based on the positive Δ V ° value is responsible. In addition, we used DAPI (Figure b, right) as a fluorescent indicator for evaluating a cell death, the dye of which intercalates into DNA of a dead cell to fluoresce.…”
Section: Resultssupporting
confidence: 69%
“…In this manner, although many groups have revealed that calcium responses in cells can be activated by mechanical stimuli such as touch and pain sensation, hearing, and particularly blood pressure through the mechanically activated cation channels over the past decade, such cellular mechanotransductions are still unknown, and thus present a quite challenging but highly significant topic for elucidating pressure effects upon the “Piezo” ion channels. To this end, we employed Fluo4-AM (Figure b, left) as a Ca 2+ -sensitive fluorescence reporter, the pressure effects of which have already been investigated . Therefore, this pair including HeLa cell and Fluo4-AM became a better choice for the present purpose, i.e ., hydrostatic pressure-regulated calcium responses through the channels in a living cell.…”
Section: Introductionmentioning
confidence: 99%
“…We investigated the dynamics of microglial volume regulation by exposing eGFP + cells to HTS while keeping the external solution's ionic strength constant (Jo et al, 2015; Ryskamp et al, 2011). These studies were conducted in dissociated cells because time‐dependent tissue swelling precludes in situ focusing and complicates the interpretation of changes in GCaMP5 fluorescence (Nakai, Ohkura, & Imoto, 2001; Schneidereit, Vass, Reischl, Allen, & Friedrich, 2016; Xiao et al, 2017). Ca 2+ ‐independent fluorescence of Fura‐2 is inversely proportional to the cell volume and thus allowed us to track water influx across the cell membrane (e.g., Jo et al, 2015, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with the idea that for indicators with a large dynamic range, the exact value of R f is insignificant [ 28 ]. For indicators such as Fluo 4, K D is often assumed to be between 0.25 and 0.5 μ M but some studies suggest that K D may have much greater range [ 60 , 61 ].…”
Section: Appendixmentioning
confidence: 99%